Design and Evaluation of a Fully Implantable Control Unit for Blood Pumps. - Unthan, Kristin; Gräf, Felix; Laumen, Marco; Finocchiaro, Thomas; Sommer, Christoph; Lanmüller, Hermann; Steinseifer, Ulrich (BioMed Research International, 2015)
As the number of donor hearts is limited while more and more patients suffer from end stage biventricular heart failure, Total Artificial Hearts become a promising alternative to conventional treatment. While pneumatic devices sufficiently supply the patients with blood flow, the patient's quality of life is limited by the percutaneous pressure lines and the size of the external control unit. This paper describes the development of the control unit of the ReinHeart, a fully implantable Total Artificial Heart. General requirements for any implantable control unit are defined froma technical andmedical point of view: necessity of a Transcutaneous Energy Transmission, autonomous operation, safety, geometry, and efficiency. Based on the requirements, a prototype is designed; it incorporates a LiFePo4 battery pack with charger, a rectifier for transcutaneous energy transmission, the motor's driver electronics, and a micro controller which monitors and controls all functions. In validation tests, the control unit demonstrated a stable operation on TET and battery supply and a safe switching from one supply to the other. The overall mean efficiency is 14% on TET and 22% on battery supply. The control unit is suitable for chronic animal trials of the ReinHeart.